2023
DOI: 10.3390/healthcare11020255
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Perception, Experience and Phobia toward Corticosteroids Use among the General Public in the Era of COVID-19: A Multinational Study

Abstract: Background: Corticosteroids play a significant role in managing the vast majority of inflammatory and immunologic conditions. To date, population-based studies on knowledge and attitudes concerning corticosteroids are scarce. This study aims to comprehensively assess knowledge, perception, experience and phobia toward corticosteroid use among the general population in the era of COVID-19. Methods: A cross-sectional self-administrated questionnaire was used to collect the data from 6 countries. Knowledge and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 63 publications
0
8
0
2
Order By: Relevance
“…(42) This can explain why women are often more knowledgeable about health-related information than men, as shown in other studies assessing the public knowledge about various health information. (43)(44)(45) With the increased competition between different brands and manufacturers of energy drinks, which is reflected by various means of advertising these products targeting mainly young people, there is a need to have awareness campaigns to counteract the peer pressure and advertisements' influence young people to decrease their consumption of energy drinks. Hence, these drinks are known for their high caffeine and sugar content, especially with the increasing number of reported caffeine toxicity cases associated with the consumption of energy drinks.…”
Section: Discussionmentioning
confidence: 99%
“…(42) This can explain why women are often more knowledgeable about health-related information than men, as shown in other studies assessing the public knowledge about various health information. (43)(44)(45) With the increased competition between different brands and manufacturers of energy drinks, which is reflected by various means of advertising these products targeting mainly young people, there is a need to have awareness campaigns to counteract the peer pressure and advertisements' influence young people to decrease their consumption of energy drinks. Hence, these drinks are known for their high caffeine and sugar content, especially with the increasing number of reported caffeine toxicity cases associated with the consumption of energy drinks.…”
Section: Discussionmentioning
confidence: 99%
“…The study questionnaire was developed after a review of pertinent validated surveys found in the literature [ 12 , 17 – 19 ] and adherence to the fundamental principles of successful survey design [ 20 ]. Through the development of the tool, a pool of questions important to the objectives of the study was added.…”
Section: Methodsmentioning
confidence: 99%
“…In order to evaluate current practices and perceptions, and to measure how close are these behaviors to corticosteroid guidelines, research efforts were put to assess perceptions, measure knowledge, and determine the actual level of corticophobia among healthcare providers [ 12 ]. In Jordan, healthcare providers tend to have certain preferences or phobias toward prescribing and dispensing corticosteroids to patients in need.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian yang kami temukan berbeda dengan hasil penelitian yang dilakukan oleh Barakat et al (2023), dimana responden pada penelitian tersebut diketahui memiliki pengetahuan yang baik meskipun responden yang menggunakan kortikosteroid hanya sekitar 31,6% dari total responden. Hal ini dikarenakan tingkat pendidikan responden, dimana 63,5% responden merupakan sarjana dan 83,6% responden hidup di wilayah perkotaan.…”
Section: Distribusi Tingkat Pengetahuanunclassified
“…Namun, obat dexamethasone tidak dapat digunakan sebagai pencegahan COVID-19 sebab penggunaan obat tidak sesuai indikasi dapat menimbulkan efek samping yang tidak diinginkan. Selain itu, peran tenaga kesehatan sangat penting dalam melakukan konseling kepada pasien secara tepat mengenai penggunaan kortikosteroid yang benar untuk mencegah keraguan, penggunaan tidak sesuai indikasi dan penyalahgunaan kortikosteroid (Barakat et al,2023).…”
Section: Distribusi Tingkat Pengetahuanunclassified